China Green Development Index Report 2011 - Li, Xiaoxi; Pan, Jiancheng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The report was launched beginning the China$1 (Bs Twelfth Five-year Period (2011-2015). After revising the measurement system of the Green Development Index 2010, the report measures the green development level of 30 provinces, municipalities and autonomous regions as well as 34 large and medium-sized cities in China. The city-based measurement is first introduced into the report. Both the province and the city Green Development Index systems consist of three parts, the green degree of economic growth, the carrying potential of natural resources and environment, and the support degree of government policies. The three parts reflect the production and resource usage efficiency, the situation of environment and resources protection and pollutants emission, and government$1 (Bs related investment and management respectively. The report also summarizes the achievements in China$1 (Bs green development during the Eleventh Five-year Period (2006-2010) and puts forward 11 special researches. The China Green Development Index Report 2011 has the highly comprehensive evaluation of the green economy development in China and its importance to China$1 (Bs rational development and switch in economic development model.s
Introduction -- SESSION 1 Green Growth of the Economy -- 1 Green Growth: Constructing a Resource-saving and Environment-friendly Production Pattern -- 2 Green Growth of the Primary Industry -- 3 Green Growth of the Secondary Industry -- 4 Green Growth of the Tertiary Industry -- 5 Measurement and Analysis of Green Degree of Economic Growth -- SESSION 2 Resource and Environment Carrying Capacity -- 6 Resource Bottlenecks and Environment Constraints in Green Development -- 7 Green Development and Resource Support -- 8 Green Development and Environmental Carrying Capacity -- 9 Green Development and Ecological Construction -- 10 Measurement and Analysis of Carrying Potential of Natural Resources and Environment -- SESSION 3 Government Green Actions -- 11 Government Actions in China$1 (Bs Green Development -- 12 Government Green Investment -- 13 Urban Infrastructure Construction and Management in Green Development -- 14 Environmental Governance in Green Development -- 15 Measurement and Analysis of the Support Degree of Government Policies -- SESSION 4 Features on Green Development -- 1 Development and Reform of Environmental Statistics -- 2 The Dilemma of Food Safety in China and Perspectives -- 3 Research on the Environmental Information Disclosure System in Sudden Environmental Pollution Incidents: Taking Zijin Mining Pollution Incident as an Example -- 4 Basic Framework for Building China$1 (Bs Green Financial System -- 5 The Significance of "Humanism" in Green Development -- 6 International Challenges Confronted by China's Environmental Problems -- APPENDIX -- Appendix 1 The Ideas, Structure and Indicators of China Green Development Index System and Measurement Methods -- Appendix 2 Explanatory Notes and Data Sources on Indicators Used to Calculate the Province Green Development Index in 2011 -- Appendix 3 Explanatory Notes and Data Sources on Indicators Used to Calculate the City Green Development Index in 2011 -- Authors and Translators.s
Keywords: Economics; Environmental law; Nature Conservation; Endogenous growth (Economics).; Economics/Management Science; Economic Growth; Nature Conservation; Environmental Law/Policy/Ecojustice.